2009
DOI: 10.1021/jp9039513
|View full text |Cite
|
Sign up to set email alerts
|

General Anesthetic Binding to Neuronal α4β2 Nicotinic Acetylcholine Receptor and Its Effects on Global Dynamics

Abstract: The neuronal α4β2 nicotinic acetylcholine receptor (nAChR) is a target for general anesthetics. Currently available experimental structural information is inadequate to understand where anesthetics bind and how they modulate the receptor motions essential to function. Using our published open-channel structure model of α4β2 nAChR, we identified and evaluated six amphiphilic interaction sites for the volatile anesthetic halothane via flexible ligand docking and subsequent 20-ns molecular dynamics simulations. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(88 citation statements)
references
References 69 publications
10
78
0
Order By: Relevance
“…Moreover, residues in the GABA A and glycine receptors have been identified that contribute to positive modulation of those receptors, using photolabeling and mutagenesis (1,3,(19)(20)(21)(22)(23)(24); some of these residues are thought to lie at the subunit interfaces in a site analogous to the intersubunit sites we observe, according to experimentally confirmed (34) homology models based on the nAChR. A similar site is occupied in simulations of halothane interacting with the nAChR (30,35). The site is highly suggestive as an allosteric modulation site, as the M2-M3 loop is thought to act in transduction of a ligand binding signal to the pore (12).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, residues in the GABA A and glycine receptors have been identified that contribute to positive modulation of those receptors, using photolabeling and mutagenesis (1,3,(19)(20)(21)(22)(23)(24); some of these residues are thought to lie at the subunit interfaces in a site analogous to the intersubunit sites we observe, according to experimentally confirmed (34) homology models based on the nAChR. A similar site is occupied in simulations of halothane interacting with the nAChR (30,35). The site is highly suggestive as an allosteric modulation site, as the M2-M3 loop is thought to act in transduction of a ligand binding signal to the pore (12).…”
Section: Resultssupporting
confidence: 61%
“…Structure-based docking is a common technique used to find ligand binding sites on a protein of known structure. Tang and coworkers (30) reported several mostly superficial sites for halothane detected using structurebased docking to their model of the α 4 β 2 nAChR in an open conformation; binding free energy calculations revealed that halothane bound with low affinity to most sites, with the exception of a deeper TM site suggested by experiments. Molecular dynamics (MD) computation-based "flooding" of the receptor (in which a high concentration of anesthetic is placed in the surrounding water and allowed to partition into lipid and protein binding sites over the course of an MD simulation trajectory) is a more expensive alternative to structure-based docking which holds several advantages for investigating volatile anesthetics and Cys-loop receptors.…”
mentioning
confidence: 99%
“…In this regard, when varenicline binds to any of the allosteric sites, it weakens this salt bridge, limiting the capping of Loop C at the hα4β2 nAChR. The same mechanism was observed for halothane at the hα4β2 nAChR, although this general anesthetic interacts with an allosteric locus near the agonist site but differs from the A1 or A2 site [59]. This suggests that varenicline, in addition to be an agonist, has negative allosteric modulatory properties at hα4β2 and hα3β4 nAChRs.…”
Section: Interactive Residuesmentioning
confidence: 85%
“…Automated docking has been used to provide initial coordinates for further unrestrained simulations[43, 85, 86], which has primarily indicated sites on the surface of the protein or at the interface between the ECD and TMD. The alternative flooding approach[87, 88] begins the simulation with a (usually high) concentration of the anesthetic dispersed randomly in the water and allows it to partition into the membrane and protein sites.…”
Section: Pharmacologymentioning
confidence: 99%
“…Although automated docking methods cannot typically be used to measure an absolute binding affinity, Bertaccini et al[90] demonstrated that automated docking scores of propofol analogs display log linear correlation with EC 50 s for GABAAr potentiation, indicating that such scores can be used to estimate relative a nities of similar compounds. Liu et al [85, 86] used AFEP to estimate absolute binding a nities of halothane for both open and closed conformations of an α 4 β 2 model of a neuronal nAChR, finding that shallow binding sites tested were low-affinity but a deeper intersubunit site indicated by experiments was moderate to high affinity. AFEP calculations of isoflurane and propofol binding to two locations in GLIC (Figure 4), the pore and the allosteric intrasubunit site indicated by crystal structures, predicted that isoflurane has higher affinity for the pore while propofol has similar affinity for the pore and intrasubunit site.…”
Section: Pharmacologymentioning
confidence: 99%